2020
DOI: 10.1371/journal.pone.0237705
|View full text |Cite
|
Sign up to set email alerts
|

Exercise influences the impact of polychlorinated biphenyl exposure on immune function

Abstract: Polychlorinated biphenyls (PCBs) are environmental pollutants and endocrine disruptors, harmfully affecting reproductive, endocrine, neurological and immunological systems. This broad influence has implications for processes such as wound healing, which is modulated by the immunological response of the body. Conversely, while PCBs can be linked to diminished wound healing, outside of PCB pollution systems, exercise has been shown to accelerate wound healing. However, the potential for moderate intensity exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…Another study reported links between PFASs, leptin and adiponectin but PA did not appear to prevent this alterations [113]. A study also demonstrated the interaction between PA and POPs on inflammatory factors but in the context of wound healing [114]. Nevertheless, this study observed that IL-1β levels, TNFα levels, CCL2 levels and IL-6 levels following PA changed in function of POPs exposure.…”
Section: The Link Between Pops Pa and Inflammatory Functionmentioning
confidence: 52%
“…Another study reported links between PFASs, leptin and adiponectin but PA did not appear to prevent this alterations [113]. A study also demonstrated the interaction between PA and POPs on inflammatory factors but in the context of wound healing [114]. Nevertheless, this study observed that IL-1β levels, TNFα levels, CCL2 levels and IL-6 levels following PA changed in function of POPs exposure.…”
Section: The Link Between Pops Pa and Inflammatory Functionmentioning
confidence: 52%
“…[ 70 ] PCBs administration also resulted in a state of oxidative stress, evident by increased lipid peroxidation and impaired antioxidant buffering capacity, demonstrated by the observed increase in testicular MDA, GSH levels, as well as a decline in glutathione peroxidase (GPx), SOD, and catalase (CAT) activities; this is in tandem with previous studies. [ 17,41,42,71 ] This study revealed that PCBs also caused testicular oxidative DNA damage as evident by increased testicular DNA fragmentation index. The free radicals induced oxidative testicular damage observed was associated with poor sperm quality, possibly due to the susceptibility of the sperm cells to peroxidative damage since they have high concentrations of polyunsaturated fatty acids as reported by several current evidence.…”
Section: Discussionmentioning
confidence: 89%
“…The induction of inflammation and oxidative stress by PCBs has been well established. [ 15,17,41,42 ] More so, the therapeutic indication of DRLC supplementation on reproductive potential has been widely documented; [ 17,21–25 ] however, the current study seems to be the first to investigate the effects of DRLC on testicular maladaptive responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported links between PFASs, leptin, and adiponectin, but PA did not appear to prevent the related alterations [116]. A study also demonstrated the interaction between PA and POPs on inflammatory factors but in the context of wound healing [117]. The study observed that IL-1β levels, TNFα levels, CCL2 levels, and IL-6 levels following PA changed the function of POPs exposure.…”
Section: The Link Between Pops Pa and Inflammatory Functionmentioning
confidence: 92%